Altered body composition, sarcopenia, frailty, and their clinico-biological correlates, in Parkinson's disease. (November 2018) - Tan, Ai Huey; Hew, Yin Cheng; Lim, Shen-Yang; Ramli, Norlisah Mohd; Kamaruzzaman, Shahrul Bahyah; Tan, Maw Pin; Grossmann, Mathis; Ang, Ban Hong; Tan, Jiun Yan; Manap, Mohamad Addin Azhan A.; Tay, Tun Khong; Tan, Siang Lyn; et al.
Abstract: Introduction: Low body weight in Parkinson's disease (PD) is poorly understood despite the associated risks of malnutrition, fractures, and death. Sarcopenia (loss of muscle bulk and strength) and frailty are geriatric syndromes that are likewise associated with adverse health outcomes, yet have received scant attention in PD. We studied body composition, sarcopenia, frailty, and their clinico-biological correlates in PD. Methods: 93 patients and 78 spousal/sibling controls underwent comprehensive assessment of diet, clinical status, muscle strength/performance, frailty, body composition (using dual-energy X-ray absorptiometry), and serum levels of neurogastrointestinal hormones and inflammatory markers. Results: PD patients were older than controls (66.0 ± 8.5 vs. 62.4 ± 8.4years, P = 0.003). Mean body mass index (24.0 ± 0.4 vs. 25.6 ± 0.5kg/m2, Padjusted = 0.016), fat mass index (7.4 ± 0.3 vs. 9.0 ± 0.3kg/m2, Padjusted <0.001), and whole-body fat percentage (30.7 ± 0.8 vs. 35.7 ± 0.9%, Padjusted <0.001) were lower in patients, even after controlling for age and gender. There were no between-group differences in skeletal muscle mass index and whole-body bone mineral density. Body composition parameters did not correlate with disease duration or motor severity. Reduced whole-body fat percentage was associated with higher risk of motor response complications as well as higher levels of insulin-growth factor-1 and inflammatory markers. PD patients had a higher prevalence of sarcopenia (17.2% vs. 10.3%, Padjusted = 0.340) and frailty (69.4% vs. 24.2%, Padjusted = 0.010). Older age and worse PD motor severity were predictors of frailty in PD. Conclusions: We found reduced body fat with relatively preserved skeletal muscle mass, and a high prevalence of frailty, in PD. Further studies are needed to understand the patho-mechanisms underlying these alterations. Highlights: Fat mass index, but not skeletal mass index, is reduced in Parkinson's disease (PD). Reduced fat is associated with higher risk of motor complications in PD. Higher levels of insulin growth factor-1 and cytokines correlate with reduced fat in PD. Frailty is highly prevalent in PD while the rate of sarcopenia is comparable to controls. Older age and worse motor severity are predictors of frailty in PD.